Pengaruh Media Pembelajaran Canva terhadap Minat Belajar Bahasa Indonesia Siswa Kelas V di SDN Kayumanis 1 - Azman AR; Andestend Andestend; Muhammad Azhar AlWahid (ALSYS, 2026)
Digital technology development requires teachers to use innovative learning media to increase students’ learning interest, particularly in Indonesian language learning in elementary schools. However, the use of digital media such as Canva in the learning process remains suboptimal, so empirical studies on its effectiveness are needed. This study aims to analyze the effect of using Canva learning media on the Indonesian language learning interest of fifth-grade students at SDN Kayumanis 1. This study used a quantitative approach with a quasi-experimental design through a nonequivalent control group design. The research sample consisted of 37 students, comprising 18 students in the experimental class and 19 students in the control class, using a total sampling technique. Data were collected using a learning interest questionnaire that had met validity and reliability tests, with a Cronbach’s Alpha value of 0.861, and were then analyzed using the Shapiro–Wilk test, Levene’s test, and an independent samples t-test. The results showed that the average learning interest of students in the experimental class increased from 73.72 to 80.78, while the control class showed relatively no meaningful change. The results of the independent samples t-test showed a significance value of 0.000 (<0.05), indicating that the use of Canva media had a significant effect on students’ interest in learning Indonesian. The conclusion of this study affirms that Canva can serve as an effective alternative digital learning medium for increasing elementary school students’ engagement and learning interest. These findings imply the importance of strengthening teachers’ competence in designing visual, interactive learning media that align with students’ characteristics.